IJCM_96A: Assessment of infant and young child feeding practices among Mothers attending maternal and child health clinic in Gulbarga Institute of medical Sciences, Kalaburagi - A Cross-sectional study - Panigrahi Sunaina; Ramesh; Shedole Dayalaxmi T; Kumar Ajay (Wolters Kluwer Medknow Publications, 2024)
Background: Infant and young child feeding is the foundation for a child's growth and development. Over a third of the undernourished children in the world live in India. A thorough comparison between NFHS 5 and its previous report suggests that, exclusive breast-feeding among infants under 6 months of age in Kalaburagi has decreased to 45.1% from 52%, which is concerning. Furthermore, the total number of children aged 6 to 24 months receiving an adequate diet is mere 15.4%. Despite strong data supporting the advantages of breast-feeding, the rate of breast-feeding is not high enough, indicating significant gaps that require identification and attention. Objectives: (1) To assess infant and young child feeding practices among mothers attending MCH clinic. (2) To determine the morbidities associated with feeding practices. Methodology: An institutional-based cross-sectional study was conducted among 400 mothers (by considering the prevalence of exclusive breastfeeding as 45.1%) of children aged 0-24 months attending the MCH clinic at Gulbarga Institute of Medical Sciences using convenience sampling technique for a period of 2 months i.e., October and November 2023. Data was collected by using the WHO IYCF practices indicators questionnaire followed by interpretation in the MS Excel sheet. Data analysis will be done by using SPSS software (version 16). The results will be expressed in terms of percentages, tables and graphs using appropriate statistical tests. Results: The overall prevalence of early (within 1 h of delivery) initiation of breastfeeding was found to be 57.75%, and that of exclusive breastfeeding among 0-6 months infants was 49%. 64% of children received continued breastfeeding at one year old, Minimum dietary diversity, Minimum meal frequency, and Minimum acceptable diet were achieved by only 28.6%, 13.20%, 13.2%. Statistically significant association between exclusive breast feeding and diarrhoea(p=<0.0001) and ARTI(p=0.0001),Bottle feeding and Diarrhoea(p=<0.0008) and ARTI(<0.05), Minimum dietary diversity and Diarrhoea(p=0.02) were found. Conclusion: Poor feeding practices among children were found to have significant association with diarrhoea and ARTI. The factors influencing IYCF practices are multifaceted, hence appropriate measures must be taken at earliest.